Voices of Asian Americans in higher education : unheard stories - Obiakor, Festus E.; Hui-Michael, Ying (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
"Voices of Asian Americans in Higher Education: Unheard Voices is a unique and historical book. Asian Americans are often portrayed as "model minority", yet their personal and educational experiences are often unheard. In this book, 10 Asian American higher education educators and scholars presented their realistic pictures in American higher education by through their personal narratives. The contributors in this book come from different regions and teach in different colleges and universities; and coincidentally, they all endure the "outsider" category formerly as students and now as professors and leaders. This "outsider" status can be emotionally overwhelming and psychologically unnerving. This status hampers opportunities for Asian Americans to grow and maximize their fullest potential. Though they develop different strategies to address their to address their "outsider" label, it is does not make it comfortable. But, time and time again, they have proven that they can succeed! In this technological age, we must value unending truths as we educate ourselves and others. We hope the book can be an educational and informational resources for administrator and faculty in higher education and educational policy makers"-- Provided by publisher.
Keywords: Asian American college teachers -- Social conditions.; Asian American college teachers -- Ethnic identity.; Minorities in higher education -- United States.; Social Science -- Cultural & Ethnic Studies -- General.; Ethnic studies.; elektronické knihy; electronic books